2002
DOI: 10.1016/s0896-6273(02)00941-8
|View full text |Cite
|
Sign up to set email alerts
|

Hsp27 Upregulation and Phosphorylation Is Required for Injured Sensory and Motor Neuron Survival

Abstract: Peripheral nerve transection results in the rapid death by apoptosis of neonatal but not adult sensory and motor neurons. We show that this is due to induction and phosphorylation in all adult axotomized neurons of the small heat shock protein Hsp27 and the failure of such induction in most neonatal neurons. In vivo delivery of human Hsp27 but not a nonphosphorylatable mutant prevents neonatal rat motor neurons from nerve injury-induced death, while knockdown in vitro and in vivo of Hsp27 in adult injured sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
188
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(198 citation statements)
references
References 58 publications
8
188
1
1
Order By: Relevance
“…For example, Benn et al[25] showed that the neuroprotective action of HSP27 is downstream of cytochrome c release from mitochondria and upstream of caspase-3 activation. On the other hand, Figueroa et al[38] demonstrated that in cortical neurons nitric oxide toxicity is mediated by mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Benn et al[25] showed that the neuroprotective action of HSP27 is downstream of cytochrome c release from mitochondria and upstream of caspase-3 activation. On the other hand, Figueroa et al[38] demonstrated that in cortical neurons nitric oxide toxicity is mediated by mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Among these proteins, special attention has been paid to a 27 kDa heat shock protein (HSP27) that is constitutively expressed in some populations of neurons. HSP27 plays an important role in cellular defense mechanisms[242526]. A previous study showed that, 1 week after avulsion of the spinal nerve root, small motor neurons (< 500 µm 2 ) negative for HSP27 immunoreactivity died and only large (> 500 µm 2 ) HSP27-positive motor neurons survived in the spinal cord ventral horn[3].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicate a role of HSP27 upregulation in motor neuronal protection and survival (Lewis et al, 1999;Benn et al, 2002;Sharp et al, 2006). The neuroprotective effects of HSP27 may be related to its involvement in neurite extension and branching (Williams et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The heat shock 27kDa protein 1 (HSP27: gene symbol HSPB1; MIM# 602195), is a member of the small heat shock protein family and is constitutively expressed in motor neurons (Plumier et al, 1997). Motor neurons upregulate the expression of HSP27 after peripheral nerve transection and this induction is crucial for their survival (Costigan et al, 1998;Benn et al, 2002;Kalmar et al, 2002). There is also increasing evidence for the neuroprotective capacities of HSP27 overexpression; e.g.…”
mentioning
confidence: 99%
“…3,6,10 Other cellular factors such as heat shock protein (HSP) 27 may be involved in regulating survival and death of neurons. 33 Thus, whether a neuron lives or dies during the period of developmental PCD may be regulated by both extrinsic (e.g., neurotrophic factors) and intrinsic (e.g. Bcl-2 members, HSP27, etc) signals.…”
Section: Discussionmentioning
confidence: 99%